Gambaran Penggunaan Obat Proton Pump Inhibitor Pada Pasien Tukak Peptikum Di Rs Royal Prima Medan Periode Januari 2022 – April 2025 - Doladave, Miguelle Franklin; Handayani, Putri; Lubis, Yolanda Eliza Putri (Syntax Corporation, 2025)
Peptic ulcer disease is a gastrointestinal disorder characterized by mucosal lesions in the stomach or duodenum. Proton Pump Inhibitors (PPIs) are the main therapy by inhibiting gastric acid secretion. To describe the use of PPI drugs in patients with peptic ulcer disease at Royal Prima Hospital Medan from January 2022 to April 2025. This descriptive retrospective study used secondary data from medical records. Samples were selected using total sampling technique, involving 96 patients who met the inclusion and exclusion criteria. Data were analyzed univariately and presented in frequency distribution. Most patients were over 50 years old (62.5%) and female (56.2%). The most commonly used PPI was lansoprazole (62.5%), with dosage of 2x1 daily (78.1%), treatment duration of 7-30 days (53.1%), and the most frequent clinical symptom was nausea (45.8%). The use of PPIs in peptic ulcer patients at Royal Prima Hospital Medan was largely in accordance with the principles of appropriate indication and dosage, with lansoprazole being the most frequently used drug.